MODEL APPRECIATIVE INQUIRY (AI) BERBASIS KEARIFAN LOKAL DALAM PENINGKATAN MUTU BERKELANJUTAN : STUDI ETNOGRAFI DI PESANTREN SALAF - Ikhsan Mubarok; Siti Aimah (As-Sulthan Journal of Education, 2026)
This study aims to analyze the application of Appreciative Inquiry (AI) based on the local wisdom of traditional Islamic boarding schools (pesantren salaf) as a strategy to improve the quality of sustainable education. The study uses a qualitative approach with an ethnographic design conducted at Pondok Pesantren Salafiyah Asy-Syafi’iyyah Darul Qur’an. The ethnographic approach is used to capture in depth the daily practices, cultural values, and the underlying meaning in the formation and maintenance of educational quality in the life of the pesantren. Data were collected through participant observation, in-depth interviews, and document studies involving key informants, including the guiding clerics (kiai), pesantren administrators, senior religious teachers (guru ngaji), and senior students (santri). Data analysis was carried out interactively through the processes of data reduction, data presentation, and drawing conclusions, while data validity was ensured through source and technique triangulation, extended researcher participation in the field, as well as member checking. The study results show that the quality of education in traditional Islamic boarding schools (pesantren salaf) is not understood as adherence to formal standards, but rather as a form of collective reflective awareness rooted in the tradition of kitab discussions, halaqah, the exemplary leadership of kiais, the value of sincerity, and khidmah. Appreciative Inquiry does not appear as a formal managerial model, but transforms into a covert cultural practice that integrates into the social structure of the pesantren, thus allowing quality improvement to occur contextually, evolutionarily, and sustainably without provoking cultural resistance. This study contributes to the development of Islamic education quality management discourse by offering a quality improvement model that is sensitive to local culture and aligns with the identity of traditional pesantren.